An Anthropological Outline of the Sutta Nipāta: The Contemplative Experience in Early Buddhist Poetry - Federico Divino (Religions, 2023)
By examining the Sutta Nipāta, considered one of the collections containing the oldest texts of the Pāli canon, this study aims to reconstruct social, historical, and anthropological aspects of archaic Buddhist doctrine at the time of its definition in dialectic with the forces of orthodoxy and constituted power in 6th century BCE India. This study also provides important insights into the development and definition of contemplative practices devoted to the search for the ‘absolute’ (paramattha and brahmavihāra), which has often received little attention in meditation studies.